Selective amide bond formation in redox-active coacervate protocells - Jiahua Wang; Manzar Abbas; Junyou Wang; Evan Spruijt (Nature Communications, 2023)
Abstract Coacervate droplets are promising protocell models because they sequester a wide range of guest molecules and may catalyze their conversion. However, it remains unclear how life’s building blocks, including peptides, could be synthesized from primitive precursor molecules inside such protocells. Here, we develop a redox-active protocell model formed by phase separation of prebiotically relevant ferricyanide (Fe(CN)6 3−) molecules and cationic peptides. Their assembly into coacervates can be regulated by redox chemistry and the coacervates act as oxidizing hubs for sequestered metabolites, like NAD(P)H and gluthathione. Interestingly, the oxidizing potential of Fe(CN)6 3− inside coacervates can be harnessed to drive the formation of new amide bonds between prebiotically relevant amino acids and α-amidothioacids. Aminoacylation is enhanced in Fe(CN)6 3−/peptide coacervates and selective for amino acids that interact less strongly with the coacervates. We finally use Fe(CN)6 3−-containing coacervates to spatially control assembly of fibrous networks inside and at the surface of coacervate protocells. These results provide an important step towards the prebiotically relevant integration of redox chemistry in primitive cell-like compartments.